1976
DOI: 10.1021/j100542a007
|View full text |Cite
|
Sign up to set email alerts
|

Ionic photodissociation of excited electron donor-acceptor systems. II. Importance of the chemical property of donor-acceptor pairs

Abstract: The relationship between the ionic photodissociation yield and the electron donor-acceptor interaction of pyrene-quencher systems was investigated by nanosecond laser photolysis and transient photocurrent measurements. While no general relation was obtained, the chemical property of donor-acceptor pairs was found to be reflected in the yield. On the basis of the present and previous results it was concluded that the ionic photodissociation process consists of two steps, namely, the encounter collisional electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…2. In the [Re 6 ] 4--PDA system, we observed transient absorption in the wavelength (k) region of 500-700 nm, which was assigned safely to the anion radical of PDA as reported by Hino et al [32]. Unfortunately, however, we could not detect the absorption band of [Re 6 ] 3-in the k region studied.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…2. In the [Re 6 ] 4--PDA system, we observed transient absorption in the wavelength (k) region of 500-700 nm, which was assigned safely to the anion radical of PDA as reported by Hino et al [32]. Unfortunately, however, we could not detect the absorption band of [Re 6 ] 3-in the k region studied.…”
Section: Resultssupporting
confidence: 69%
“…4 /M/cm [32], we evaluated the decay time constant of the PDA anion radical to be 2.7 9 10 8 /M/s. As a reference system producing an electrostatically-attractive product ion pair by PET, we also studied transient absorption of a pyrene (Py)-PDA system as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(1972) noted rapid drop-off in ion yield with solvent polarity in the pyrene-dimethylaniline system when W' = E; -EA exceeded Wr'] = W* -U [ * ] . In reactions of pyrene with a number of acceptors in acetonitrile, Hino et al (1976) found that the yield of ions increased as the energy of the ion pair calculated by Eq. 23 increased.…”
Section: Molecules Primarily Of Photochemical Interestmentioning
confidence: 99%
“…Of particular relevance are small-molecule radical ions, which have shown interesting reactivity in protic media. Importantly, these photogenerated radicals are neither the result of electronic transitions that occupy a high-lying orbital by depopulating a low-energy orbital in the same molecule nor the outcome of molecular cleavage (Scheme ). The study of photogenerated charged organic radicals impulsively generated in solution via photolysis of π-stacked CT complexes dates back to their use as a testing ground for Marcus electron transfer theory and as model systems for exciplexes. Photogenerated ion pairs have been shown to possess strongly environment-dependent properties affecting the yield and recombination rates of free ions, as well as the ability of charges to either be localized or delocalized over several molecules . Therefore, photolysable CT complexes of substituted aromatic molecules in solution represent an ideal system to study the evolution of radical ions in their ground electronic state.…”
Section: Introductionmentioning
confidence: 99%